A Game Modeling of a Closed-loop Supply Chain in a Water-energy Nexus: Technology Advancement, Market Competition and Capacity Limit - (:unkn) unknown (My University, 2019)
Water and energy are two scarce and concerning resources interconnected in the water-energy nexus. In the nexus, production of energy needs water, and production of water needs energy. For better management of these resources in the nexus, this research considers a supply chain that consists of water suppliers, power suppliers, and consumers of these commodities. In the chain, water suppliers purchase power from power suppliers, and power suppliers purchase water from water suppliers. Other consumers can also buy these resources at the water and power markets. Each firm tries to maximize its own profit. The suppliers of water and power decide their production quantities. The prices of the commodities depend on the quantities supplied to the market, observing that a firm's profit is dependent not only on its own decision, but also on the decision of the other firms for their production quantities. The interaction of the firms in the supply chain is modeled as a simultaneous game. Four different market structures (i.e., models) are introduced in this research. The first model considers a monopoly power market and and a monopoly water market. In this model, we find the Nash equilibrium and analyse various economic measures. We also investigate the effect of technology efficiency on the same market as well as on the cross market. In the second model, we consider a duopoly in the water market, where the two firms are identical. The purpose of this model is to investigate the effect of market competition on the firms of the same industry and the firms of the cross industry. The third model generalizes the second model by considering oligopoly markets with identical firms. Another assumption of the above models, besides their being identical, is that the firms do not have capacity limits. In the last model, we relax these assumptions and consider that power suppliers may own more than one generating unit (i.e., power plant). A case study is considered with different scenarios to investigate the effect of technology efficiency and capacity limits. In these models, we find the Nash equilibria and derive various economic measures. The analysis shows that there are unique Nash equilibria under some conditions and multiple Nash equilibria under other conditions. When there are multiple equilibria, a government can provide incentives so that the firms can choose a Pareto optimal decision for the benefit of all entities involved. We find that depending on the conditions of the markets, technology improvement does not always lead to better outputs and better economic measures. When there are enough supplies for the firms and consumers to purchase, improvement of production technology for reduced water and power consumption also improves all economic measures of the supply chain, including social welfare. Under the same condition, higher competitions in the water or energy industry also improve all economic measures. However, when either the water or the power supply is solely consumed by the firms in the cross industry, the improvements of technology and higher competition can give negative effects on some measures. When an industry has a new entrant (competitor), the incumbent firms may earn higher profits if the technology inefficiency remains above 60%. While more efficient firms may have a competitive advantage to produce more, a limited capacity may shift this competitive advantage to less efficient firms if they have higher capacity limits when demand is high.
Keywords: Cournot competition in nexus; game theory; mixed complementarity problem; water-energy nexus; water-energy supply chain